Generation Z Girls and the Quest for Authenticity: A Psychological Perspective - Derakhsh , Ali; Alizadeh Damie, Touran; Seifsadat , Zahra; Barzgar , Shabnam (Psychology of Woman Journal, 2024)
Objective: This study aims to explore the quest for authenticity among Generation Z girls in Tehran, Iran, through a psychological perspective. Methods and Materials: The study employed a qualitative research design using a phenomenological approach. Data were collected through semi-structured interviews with 26 female adolescents aged 15 to 20 years from various high schools and universities in Tehran. The interviews, conducted in Persian, were transcribed verbatim and analyzed using thematic analysis to identify key themes and subthemes related to authenticity. Findings: Four main themes emerged from the analysis: understanding authenticity, challenges to authenticity, strategies for maintaining authenticity, and the impact of authenticity on well-being. Participants described authenticity as being true to oneself and influenced by social factors, emotional connections, and role models. Challenges included social media impact, societal expectations, internal conflicts, balancing relationships, and external pressures. Strategies for maintaining authenticity involved self-reflection, support systems, boundary setting, positive reinforcement, adaptive coping mechanisms, and engaging in authentic activities. Authenticity positively impacted mental health, social relationships, academic and career success, personal growth, and overall life satisfaction. Conclusion: The quest for authenticity is a central aspect of the psychological and social development of Generation Z girls in Tehran. Despite numerous challenges, these adolescents employ various strategies to maintain their authenticity, which significantly enhances their well-being. Understanding the factors that influence authenticity and supporting authentic self-expression can help foster resilience and personal growth among Generation Z girls.